2017
DOI: 10.2147/dddt.s125349
|View full text |Cite
|
Sign up to set email alerts
|

MC-PPEA as a new and more potent inhibitor of CLP-induced sepsis and pulmonary inflammation than FK866

Abstract: Our previous study indicated that overexpression of nicotinamide phosphoribosyltransferase (NAMPT) aggravated acute lung injury, while knockdown of NAMPT expression attenuated ventilator-induced lung injury. Recently, we found that meta-carborane-butyl-3-(3-pyridinyl)-2E-propenamide (MC-PPEA, MC4), in which the benzoylpiperidine moiety of FK866 has been replaced by a carborane, displayed a 100-fold increase in NAMPT inhibition over FK866. Here, we determined the effects of MC4 and FK866 on cecal ligation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
(64 reference statements)
0
7
0
2
Order By: Relevance
“…A NAMPT inhibitor analog, meta-carborane-butyl-3-(3-pyridinyl)-2E-propenamide (MC-PPEA, MC4), was synthesized by replacing the benzoylpiperidine moiety in FK866 with meta-carborane [46]. MC4 also showed inhibitory effects on cecal ligation and puncture (CLP)-induced mortality, TNFα levels, pulmonary myeloperoxidase activity, alveolar injury, and IL-6 and IL-1β messenger RNA levels [47]. Taken together, we discovered that LPS or CASP induced visfatin protein expression and ensured STAT3 or NF-κB activation and induced downstream inflammatory cytokines expression, and this was further confirmed in the cell model (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…A NAMPT inhibitor analog, meta-carborane-butyl-3-(3-pyridinyl)-2E-propenamide (MC-PPEA, MC4), was synthesized by replacing the benzoylpiperidine moiety in FK866 with meta-carborane [46]. MC4 also showed inhibitory effects on cecal ligation and puncture (CLP)-induced mortality, TNFα levels, pulmonary myeloperoxidase activity, alveolar injury, and IL-6 and IL-1β messenger RNA levels [47]. Taken together, we discovered that LPS or CASP induced visfatin protein expression and ensured STAT3 or NF-κB activation and induced downstream inflammatory cytokines expression, and this was further confirmed in the cell model (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…3b). Our finding that the formation of Rankl-stimulated TRAP + cells was blocked by treatment with the small molecule Nampt inhibitors, FK866 12 or MC4 13,20 , provides evidence for the requirement of NAD + in osteoclastogenesis. In addition, the increased inhibitory effect of an MC4 + MTX combination relative to individual treatments of each drug, support our earlier work which demonstrated that the inhibition of NAMPT potentiated the effectiveness MTX 21 .…”
Section: Discussionmentioning
confidence: 61%
“…These cell lines represent suitable models to study the lineage fate determination of multipotent stem cells [ 24 , 25 ]. Although Nampt could promote osteogenesis, which may be a target for osteoporosis treatment, it is noticeable that Nampt could act as double-edged swords since its expression is upregulated during inflammation, as NAMPT represents a novel clinical biomarker in acute lung injury [ 26 ], rheumatoid arthritis [ 27 ], Crohn’s disease [ 28 ], and inhibition of Nampt activity attenuates the CLP-induced sepsis in mice [ 29 ]. Like some other genes, Nampt’s function is likely dependent on cellular and genetic context.…”
Section: Discussionmentioning
confidence: 99%